2010
DOI: 10.5713/ajas.2010.90444
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protease-resistant Antimicrobial Substances Produced by Lactic Acid Bacteria on Rumen Methanogenesis

Abstract: Effects of protease-resistant antimicrobial substances (PRA) produced by Lactobacillus plantarum and Leuconostoc citreum on rumen methanogenesis were examined using the in vitro continuous methane quantification system. Four different strains of lactic acid bacteria, i) Lactococcus lactis ATCC19435 (Control, non-antibacterial substances), ii) Lactococcus lactis NCIMB702054 (Nisin-Z), iii) Lactobacillus plantarum TUA1490L (PRA-1), and iv) Leuconostoc citreum JCM9698 (PRA-2) were individually cultured in GYEKP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…The effect of the LP80 supernatant in combination with P. productus was also studied in vivo using two rams and it was concluded that inhibition of methanogenesis (80% decrease; mmol/6 h) occurred during the first 3 days but the effect did not persist. Compounds (PRA1) produced by L. plantarum TUA1490L were tested in vitro and found to decrease methanogenesis by 90% (Asa et al, 2010). Further work with PRA1 confirmed its ability to maintain an antimicrobial effect even after incubation with proteases but the hypothesis that the inhibition mechanism of PRA1 may relate to the production of hydrogen peroxide has not been proven (Takahashi, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the LP80 supernatant in combination with P. productus was also studied in vivo using two rams and it was concluded that inhibition of methanogenesis (80% decrease; mmol/6 h) occurred during the first 3 days but the effect did not persist. Compounds (PRA1) produced by L. plantarum TUA1490L were tested in vitro and found to decrease methanogenesis by 90% (Asa et al, 2010). Further work with PRA1 confirmed its ability to maintain an antimicrobial effect even after incubation with proteases but the hypothesis that the inhibition mechanism of PRA1 may relate to the production of hydrogen peroxide has not been proven (Takahashi, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a protease‐resistant antimicrobial compound (PRA‐1) is produced by Lactobacillus . Lactobacillus plantarum TUA1490L is capable of inhibiting or reducing methane production (Takahashi et al ; Asa et al ). However, there is little or no information on the use of Lactobacillus farciminis on ruminant fermentation activity, especially their impacts on production of biogases.…”
Section: Introductionmentioning
confidence: 99%
“…Nisin obtained from Lactobacillus lactis ssp. Recently, highly specifi c antibacterial activity of PRA-1 produced by Lactobacillus plantarum TUA1490L against methanogens was reported by Asa et al ( 2010 ). It is nearly as potent a methane inhibitor as monensin, and it was just as effective in decreasing the acetate to propionate ratio and has been reported that 36 % methanogenesis was reduced by the use of nisin (Callaway et al 1997 ).…”
Section: Use Of Bacteriocinsmentioning
confidence: 99%